2016
DOI: 10.1186/s40317-016-0103-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-tagging behaviour and habitat use in shortnose sturgeon measured with high-frequency accelerometer and PSATs

Abstract: Background: External tagging of fish using pop-up satellite tags (PSATs) can cause trauma and stress associated with capture, handling, tagging injury and tag placement that impedes body function and mobility, and these can affect the behaviour of the fish. We measured short-term (days) post-release behavioural response of estuarine shortnose sturgeon to tagging with PSATs and high-frequency accelerometers. Methods:We developed a secure, low-noise attachment method for high-resolution (50 Hz) accelerometer PSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 65 publications
(106 reference statements)
0
15
0
Order By: Relevance
“…Fortunately, since the early 2000s, awareness of capture and tagging-related effects on animals has grown with researchers using various approaches to tackle potential problems (McMahon et al 2011;Vandenabeele et al 2015;White et al 2013). While some studies found no evidence for such effects (McMahon et al 2008;Ropert-Coudert et al 2009), others showed tagging-related impacts ranging from physiological effects, such as changes in cortisol levels (Cattet et al 2014) or capture myopathy (Höfle et al 2004;Ponjoan et al 2008), to behavioural effects including changes in movement and space use (Morellet et al 2009;Rachlow et al 2014) or generally reduced activity (Broell et al 2016;Dennis and Shah 2012). Tagging effects may accumulate over time and can have detrimental influence on life history parameters such as reproductive success or survival rate (Barron et al 2010;Blanchet et al 2014;Casas et al 2015), or may only be shorttermed and diminish over time (Dennis and Shah 2012;Morellet et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, since the early 2000s, awareness of capture and tagging-related effects on animals has grown with researchers using various approaches to tackle potential problems (McMahon et al 2011;Vandenabeele et al 2015;White et al 2013). While some studies found no evidence for such effects (McMahon et al 2008;Ropert-Coudert et al 2009), others showed tagging-related impacts ranging from physiological effects, such as changes in cortisol levels (Cattet et al 2014) or capture myopathy (Höfle et al 2004;Ponjoan et al 2008), to behavioural effects including changes in movement and space use (Morellet et al 2009;Rachlow et al 2014) or generally reduced activity (Broell et al 2016;Dennis and Shah 2012). Tagging effects may accumulate over time and can have detrimental influence on life history parameters such as reproductive success or survival rate (Barron et al 2010;Blanchet et al 2014;Casas et al 2015), or may only be shorttermed and diminish over time (Dennis and Shah 2012;Morellet et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such tagging effects can be assessed via direct observations of tagged individuals (Gendron et al 2014) and/or a control group (Authier et al 2013;RopertCoudert et al 2007), by measuring physiological parameters such as blood sampling (Montané et al 2002;St. Aubin et al 2013) or by using the logged data itself (Broell et al 2016;Rachlow et al 2014). A particular value of bio-logged data for examining tagging effects is that it is effectively seamless and has high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional telemetry (acoustic pingers) has been used to assess handling effects on lake (Hondorp, Holbrook, & Krueger, 2015) and Atlantic (Balazik, 2015) sturgeon. Our data indicated that the addition of activity sensors provides a more detailed account of fish behavior and could be used to document subtle changes in behavior following capture and handling (Broell et al, 2016;Watanabe et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…Recent at‐sea studies to document green sturgeon mortality after capture in the California halibut ( Paralichthys californicus) trawl fishery have used pop‐off satellite transmitters (unpublished data, P. Doukakis, National Marine Fisheries Service). Teaming this technology with accelerometer records would provide a more detailed portrayal of sub‐lethal effects of capture and could provide estimated time to recovery for individual fish (Broell et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation